CBT for Childhood Anxiety: Reviewing the State of Personalised Intervention Research - Bertie, Lizél-Antoinette; Hudson, Jennifer L. (Frontiers in Psychology, 2021)
This article presents a mini review of the state of personalised intervention research in the field of child and adolescent anxiety. We evaluated narrative, systematic, and meta-analytic reviews of key research methodologies and how they relate to current approaches for personalising CBT, specifically. Preliminary evidence of predictors (severity of primary disorder, social anxiety disorder (SoAD), comorbid depression, parental psychopathology, parental involvement, and duration of treatment), moderators (type of primary disorder), and mediators (self-talk, coping, problem solving, comorbid symptoms) of CBT outcomes provide content for several personalised approaches to treatment. Finally, we present a novel conceptual model depicting the state of personalised intervention research in childhood anxiety and propose a research agenda for continued progress.